Łączenie się giełd w procesie globalizacji - Łobodziński, Emil (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The process of globalization and mergers is evident around the world. It applies not only to international corporations but also to the financial market and especially to stock exchanges. There are several reasons why different exchanges decide to merge. The most important are: competition, potential savings, interest of shareholders. When two or more exchanges merge it influences the financial market, both in positive and negative way. Savings and increased liquidity are benefits while potential for monopolization in regional scale is a threat. In recent years, there have been several big, transatlantic mergers with NYSE-Euronext and Nasdaq-OMX as an example. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 287-296